Impact of lumbar pedicle screw positioning on screw stability - A biomechanical investigation. (April 2020) - Grevenstein, David; Scheyerer, Max J.; Meyer, Carolin; Borggrefe, Jan; Hackl, Michael; Oikonomidis, Stavros; Eysel, Peer; Prescher, Andreas; Wegmann, Kilian
Abstract: Background: Screw loosening is a major complication following spondylodesis. While several modifications increase screw stability, some, such as screw augmentation, are associated with potential complications; new techniques are needed to minimize the risk of screw loosening without increasing complication rates. Methods: 13 fresh-frozen human lumbar vertebral bodies (L1 to L5) were dissected. In group 1 (n = 7), pedicle screws were implanted conventionally, while in group 2 (n = 6), the screws were positioned divergent in the sagittal pathway. Screw stability was tested under cyclic axial load; one testing-cycle included 1000 repetitions. The first cycle started with a load of 100 N while the load was increased by +20 N in each following cycle until failure. Failure was defined by either a >5 mm movement of the screw heads or triggering of the switch-off threshold. Findings: Average number of cycles until failure was increased in group 2 compared with group 1 (12, 046 vs 9761 cycles), as was the average load to failure (Fmax 313 N vs 260 N). Overall, in group 2, the number of cycles until screw loosening or failure increased by 23% (p = 0.28), while the required force increased by 20% (p = 0.3). Statistically significant correlation between BMD and increased number of cycles completed as well as with increased load (p < 0.01) could be observed. Interpretation: The results demonstrate, that divergent screw-drift of pairs of screws in the sagittal plane tends to increase stability, especially in vertebral bodies with lower bone density. Moreover, we could demonstrate a correlation between BMD and stability of screw-fixation. Highlights: Lumbar parallel screw fixation is commonly used for strength and stability. This study tested a new, diverging screw fixation technique. Fresh-frozen vertebral bodies were used to compare parallel and diverging screw fixation. Diverging screw fixation tends to offer more strength and stability in poor bone-quality.